CONJOINE ANALYSIS TO MEASURE TOURIST PREFERENCES IN SA'DAN TO' BARANA TOURIST OBJECT, NORTH TORAJA REGENCY - Parrangan, Daniel; Kurniasari Wibisono , Lisa; Marchelin , Marchelin (Universitas Islam Lamongan, 2025)
The strategy for tourism development in Sa'dan To'Barana' was previously based on general assumptions without the support of quantitative data reflecting specific tourist preferences. This study aims to analyze tourists' preferences for the attributes of Sa'dan To'Barana' tourist attraction in North Toraja Regency using the conjoin analysis method. Quantitative methods were used in this study with surveys and questionnaires as the main tools whose results were statistically analyzed. The research population was tourists who visited Sa'dan To'Barana' tourist attraction between December 2024 and January 2025. The research sample consisted of people who had visited the tourist attraction. This study involves two variables: independent variables (tourist attraction attributes) and dependent variables (tourist preferences). The results show that accessibility and entrance fees are the two main factors that most influence tourists' preferences, both of which are more important than tourist facilities and management services. Correlation analysis showed a very strong relationship between observed and predicted preferences, with Pearson's R value of 0.947 and Kendall's tau of 0.768, both of which indicated significant positive correlations. These findings provide a basis for tourism managers to formulate more appropriate development strategies based on travelers' preferences.